Development of bottled oyster (Cassostrea sp.) in oil - Obligar, Pepito Arollado Jr. (Iloilo College of Fisheries and Ocean Sciences, U.P. Visayas, 2006)
The primary objective of this study is to develop an acceptable method of processing for bottled oyster. Several formulations include the development of bottled oyster in brine, in oil and in oil with species added,. The formulated products were evaluated through sensory evaluations by a group of laboratory six (6) semi-trained panellists. The product with the highest rank for general acceptability was adapted in the further product development processes. The filling weight of the product was standardized to avoid slacking filled bottles and ensure uniformity. A heat penetration study was conducted in standardization of the processing time and temperature combinations for the best formulated product to determine the lethality of the process applied. Thermal processing schedule was standardized at 115 degree C ((10psi). sensory, chemical and microbiological evaluation processes were employed on the final product to determine the effect of processing methods in the quality and safety of the oyster. Among the products tested, the bottled oyster in the oil with species had the highest rank for genera acceptability and was therefore considered to be the final product and adapted in the succeeding product development. The processing schedule determined as 40 minutes at 115.6 degree C was found appropriate to produce a safe and acceptable product. Chemical evaluation using TVB-N showed that TVB-N content of the sample was less than 20mg N per 100g samples, the USFDA acceptable limit for food products. This result suggest that the product was fresh and of good quality. Likewise, the result of microbiological evaluation is negative for gas forming microorganism, which indicates that the product is considered to be safe and does not support the growth of C. botulinum. A further study to improve the texture of the product can be undertaken by reducing the heat treatment provided that the minimum F0 value required for the product is meet to [produce safe and quality product. To give preference in processing, other processing schedule should also be evaluated and standardized for the product. Thermal death time studies of the formulated product must be pursued in order to verify results.
Thesis -- B.S. -- U.P. Visayas
Keywords: Bottled Oyster; Cassostrea sp; Oil